Marketing Mix dalam Dual Persepektif (Konvensional dan Syariah) - Anwar, Moh Muhlis (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2022)
Islam is a religion that has economic and business structures that are clearly defined and have demonstrated their usefulness and power. In reality, Islam is a religious religion which cannot be detached from the realities of daily human actions, either spiritual, social or commercial. Given the situation that business transactions are part and parcel of human everyday activities, Islam provides a framework that defines the moral and ethical behaviour of all commercial efforts. the notion of the marketing mix and four P’s have been extremely dominant paradigms marketing stage for many firms. With this in mind, the research seeks to highlight the significant elements of the Islamic perspective on the framework of marketing mix. The study evaluates the four Ps of marketing mix which are product, pricing, promotion, location and people from the perspective of Islam. The study employs the technique of examining the prevalent methods of marketing mix from an Islamic viewpoint with the only purpose to emphasize the efficacy and strength of an Islamic ethical framework